Panitia Seminar Nasional Kimia - Widodo, Nanang Tri (PROSIDING SEMINAR NASIONAL KIMIA; Vol 1 No 1 (2022): Prosiding SNK 2022, 2022)
Pengarah Dr. Eng. Idris Mandang, M.Si Prof. Dr. Bohari, M.Si Penanggung Jawab Dr. Sri Wahyuningsih, M.Si Dr . Yanti Puspita Sari, M.Si Dr. Rudi Kartika, M.Si Ketua Moh. Saiful Arif, S.Pd. M.Si Sekretaris Djihan Ryn Pratiwi, M.Si  Siti Maisarah, S.Pd Bendahara Dr. Winni Astuti, M.Si Anggota Dr. Saibun Sitorus, M.Si Dr. Subur P. Pasaribu, M.Si Dr. Ir. Erwin, M.Si Dr. Chairul Saleh, M.Si Dr. Ritbey Ruga, M.P., Ph.D Alimuddin, M.Si Ritson Purba, M.Si Husna Syaima, M.Si Irfan Ashari Hiyahara, M.Si Veliyana Londong A, M.Si Ika Yekti Lianasari, M.Si Rita Hairani, M.Sc Nanang Tri Widodo, M.Si Ahmad Maulana, S.Si Muhammad Fadlianur, S.Si Arbain Wawinca, SE Rahman Raya, S.Pd Manja’a Khasanah,S.Si